2014
DOI: 10.1007/s10826-014-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Positive Parenting Through Metacognition with the Program ‘Lou & us’

Abstract: This study used a micro-trial design to evaluate 'Lou & us', a 3-week parenting program based on metacognition. The program consists of sessions using a CDRom and interviews with the program deliverer. The study tested whether and to what extent the program is effective in enhancing positive parenting, in particular childrearing behavior, self-efficacy beliefs and co-parenting. In Study 1, the program was used by French-speaking mothers and fathers in a community-based sample of 152 families. Study 2 was a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…In a French‐speaking area of Belgium, Roskam () evaluated Lou & Us, a self‐guided education programme that aimed to enhance positive parenting via meta‐cognitive skills in parents of children aged between 4 and 7 years. The programme was delivered via CD‐ROM, in conjunction with interviews facilitated by trained Masters students to help parents develop insights into their parenting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a French‐speaking area of Belgium, Roskam () evaluated Lou & Us, a self‐guided education programme that aimed to enhance positive parenting via meta‐cognitive skills in parents of children aged between 4 and 7 years. The programme was delivered via CD‐ROM, in conjunction with interviews facilitated by trained Masters students to help parents develop insights into their parenting.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six trials to examine dysfunctional parenting practices such as parent–child aggression and intrusiveness, four did not show effects (Florsheim et al., ; Frank, Keown, & Sanders, ; Petch et al., ; Roskam, ), one trial reported mixed findings (Feinberg & Kan, ; Kan & Feinberg, ) and one reported improvements (Stover, ). Four trials examined parenting efficacy, which refers to the beliefs parents hold about their ability to parent successfully.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent micro-trials have targeted cognitive Roskam, 2015) or behavioral parenting variables (Brassart & Schelstraete, 2015b;) in a specific onevariable format. The efficacy of specific parenting interventions has also been tested among parents of clinically referred children (Brassart & Schelstraete, 2015a).…”
Section: Parenting Program Formatsmentioning
confidence: 99%